Predicting factors leading to cardiac arrest in solid organ transplant recipients: a retrospective analysis of code blue patients - Acharya, Subhash P.; Hawryluck, Laura; McCluskey, Stuart; Steel, Andrew (Journal of Chitwan Medical College, 2018)
Background: Cardio Pulmonary (Code Blue) arrests in solid organ transplant recipients are particularly distressing events in view of the tremendous investment by organ donors, families, and by the healthcare system. Methods: After ethical approval, all code blue events occurring in solid organ transplant patients were identified from Critical Care Response Team (CCRT) database and the code blue resuscitation records from 2007-2011. All patients who sustained cardio-respiratory arrests were included. Resuscitation records were also explored to identify quality, duration and immediate event and outcome. Results: Over the five-year period, there were 63 code blue calls in solid organ transplant patients out of which only 27 (n=27) were actual code blue arrest requiring resuscitation. The frequency was highest in liver transplant (10), followed by lungs (8), kidney (5), double organ (kidney + liver/lung = 2), and heart (1), and one patient with Liver transplantation had arrested twice. Seventeen (62.96%) of these patients were in the ward while 10 (37.04%) were in the step-down unit (SDU) when the arrest occurred. Most of them (16, 59.25%) were attended by a nurse within 30-mins prior to the code. Factors associated in these code blue patients were documented source of infection (11, 40.74%), blood transfusion (7, 23.9%), surgical event as cause of arrest (6, 22.22%), procedures within 24 hours (6, 22.22%) and dialysis within 24 hours (5, 18.51%). It was also found that serum magnesium was low on almost all patients. Conclusion: Even though the frequency of code blue events in solid organ transplant patients was not high, it was concerning that in many events with prior warning signs of deterioration did not result in CCRT being called. However resuscitations were prolonged reflecting the teams’ investment in this patient population. This study thus highlights the importance of early involvement of CCRT in these patients.